PENGARUH ATRIBUT PRODUK TERHADAP LOYALITAS PELANGGAN GREEN PRODUCT SEPEDA MOTOR HONDA INJECTION (Universitas Negeri Semarang, 2012)
Product attributes influence quality, design, color, label, and the aesthetics dimensions toward green product injection Honda motorcycle customers loyalty partially or simultaneously is needed to be known to measure customers loyalty. So, this researched is conducted to find that data. Based on the result, it shows that quality dimension has probability value thitung 4,224 with sig. Hitung 0,000 < 0,05, design dimension has probability value thitung - 0,634 with sig. Hitung 0,530 > 0,05, color dimension has probability value thitung - 1,624 with sig. Hitung 0,213 > 0,05, label dimension has probability value thitung 2,371 with sig. Hitung 0,023 < 0,05, aesthetic dimension has probability value thitung 2,415 with sig. Hitung 0,020 < 0,05. While the result of simultance Fhitung 4,100 with sig. 0,004 < 0,05. This data shows that there is influence of quality, design, color, label and aesthetic dimension simultaneously towards customer loyalty to green product injection Honda motorcycle. Partially, it can be known that the dimensions of quality, label, and aesthetic of product attributes influence green product injection Honda motorcycle.